Exploring competency-based medical education among specialist doctors in Malaysia - Tukiman, Nur Fariza; Zainal Abiddin, Norhasni (2017)
This research was done with the objective to explain the development process of medical specialist when they went through continuous learning process via the Continuing Professional Education (CPE) upon being recognized as a medical specialist. The main elements that are related to the expertise development will also be discussed in greater detail. This study presents the findings from in-depth interviews with medical specialists which explore the competency-based medical education in the context of continuing professional education. The data of this research had been collected by way of semi structured interview from 10 selected informants actively practicing medical specialists in various field of medical expertise. All data have been analysed using the ATLAS.ti. From the analysis, six themes have been identified in the expertise development process of a medical doctor. The themes relate to the competency that is required as a specialist in their respective areas. The themes are (i) patient care; (ii) medical knowledge; (iii) practice-based learning and improvement; (iv) system-based practice; (v) professionalism and (vi) interpersonal skills and communication. The research outcome has also shown that the medical knowledge changes continuously. Therefore, it is the responsibility of all doctors to continuously learn and improve their knowledge from time to time to ensure that they are not left out, especially in the new medical knowledge areas.